Attitűd – cselekvés – környezeti állapot modell. A Balaton déli vízgyűjtőjének konfliktusvizsgálatához - Horváthné Kovács, Bernadett; Nagy, Mónika Zita (Acta Scientiarum Socialium, 2013)
Attitude – action – environment model for the conflict analysis of the southern catchment area of Lake Balaton The current paper reviews mathematical-statistical modelling options for conflict analysis of the catchment area of given shallow lake. On the basis of primary and secondary researches the actors and their features are being defined, which determine the mathematical-statistical system. Considering the tool kit of statistical modelling, the databases gained in the course of preliminary researches and the recommendations of reviewed literature the frames of a potential stochastic model are introduced. The authors underline that the current paper deals with the theoretic grounding ofthe mentioned model.